2018
DOI: 10.1111/jop.12718
|View full text |Cite
|
Sign up to set email alerts
|

Does Hypoxia‐Inducible Factor ‐1 α (HIF‐1α) C1772T polymorphism predict short‐term prognosis in patients with oral squamous cell carcinoma (OSCC)?

Abstract: Our study showed that CT genotype for C1772T polymorphism of HIF-1α predisposes to aggressive tumor phenotype in patients with OSCC. Moreover, patients with CT genotype had poor survival rate as compared to CC genotype. A cut-off value of 460 pg/mL of HIF-1α can help to segregate patients with OSCC from healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…2 Forest plot for the association of the HIF-1α C1772T polymorphism and HNC risk under a recessive genetic model Fig. 3 Forest plot for the association of the HIF-1α G1790 polymorphism and HNC risk under the allele genetic model stratified by source of control inconclusive [32,34,[36][37][38][39][40]. This might be because of the limitations of these studies, such as ethnic differences, control source differences, small sample sizes and different methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Forest plot for the association of the HIF-1α C1772T polymorphism and HNC risk under a recessive genetic model Fig. 3 Forest plot for the association of the HIF-1α G1790 polymorphism and HNC risk under the allele genetic model stratified by source of control inconclusive [32,34,[36][37][38][39][40]. This might be because of the limitations of these studies, such as ethnic differences, control source differences, small sample sizes and different methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no studies have evaluated HIF-1αC1772T in the progression of HNC. In this meta-analysis, seven studies were ultimately enrolled for the C1772T polymorphism [32,34,[36][37][38][39][40], and six studies were included for the G1790A polymorphism [32,34,[37][38][39][40]. Overall, the results demonstrated that the HIF-1α C1772T polymorphism is an important factor in determining the increased risk of HNC (OR = 2.27, 95% CI = 1.17-4.42 for the homozygous model; OR = 11.53, 95% CI = 1.11-120.4 for the recessive model).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations